O impacto de crises financeiras e de medidas prudenciais adotadas pelo Banco Central do Brasil no desempenho bursátil e contábil dos bancos brasileiros no período de junho de 2008 a junho de 2012 - Araes, Theresângela Giongo Flores (2013)
The bankruptcy of Lehman Brothers in 2008 rapidly provoked a severe systemic risk in the global banking industry and resulted in the worst financial crisis since the Great Depression in 1929. This crisis affected the Brazilian Financial System, contributing to the adoption of several prudential measures to soften their effects. As a consequence of such crisis, the European fiscal crisis started in mid-2010, with new expansive measures being adopted in Brazil in 2011. This study evaluated how these international financial crises and prudential measures adopted by the Brazilian Central Bank affected the stock and the financial performance of Brazilian Banks. It was used the methodology of event study and of financial analysis based on the evaluation of accounting indexes, which are traditional in the banking system (CAMELS). It was noticed that the stock performance of the banks, in general, was not statistically affected by the selected events. This behavior can be partially explained by the dynamic nature of the events, which only happen after consecutive disclosure of relevant information about the economic environment and the companies to the market. Regarding the financial performance, it was noticed that, in moments of crises, the banks adopt a more conservative posture towards credit concession, due to higher delinquencies and lower profitability. Banks focus on improving their liquidity conditions. Despite overall negative impact of financial crises over the banks profitability and asset quality of Brazilian Banks, the strong capital structure of the banking system allowed the absorption of such losses